2y-2y=5y

Simple and best practice solution for 2y-2y=5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-2y=5y equation:


Simplifying
2y + -2y = 5y

Combine like terms: 2y + -2y = 0
0 = 5y

Solving
0 = 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
0 + -5y = 5y + -5y
Remove the zero:
-5y = 5y + -5y

Combine like terms: 5y + -5y = 0
-5y = 0

Divide each side by '-5'.
y = 0

Simplifying
y = 0

See similar equations:

| 5cosx-sinx+4=0 | | 15x-0.75=13x-0.50 | | 18t+4(1t+5)=42 | | (t+10.5)+2t+t=180 | | 3(x+5)-5=2(2x-4)-1x | | 5n+20=4n+16 | | x^2+4+x^2+x= | | X+7=8x-14 | | 3y-7x+9=0 | | (s)2(s+3)+(4s-5)=148 | | 5.5-x=(-4.5-x) | | 7y-7=6y+13 | | 18-4k=-10-k | | -14=2x+-24 | | (3k+4)x-(2k-6)y=-10 | | 4a-8=8a-(4a+8) | | 2n+18=3n+37 | | x^2-14x+360=0 | | -10(10n-9)+6(-5n+7)= | | 310=3x-8(8x+7) | | 2(x+1)-1=11 | | c=38.34+0.50 | | 5x-2(x-3)=4x+15 | | 11d-10=6d | | N-6n= | | 4m^2n+(-m^2n)=0 | | 4m^2n+(-m^2n)= | | 0.1*x+0.25(5x)=5.25 | | log=0.45 | | 0.85x=612 | | (6x-10)+(6x+10)=18 | | 5(7x+1)=5+2x |

Equations solver categories